2020
DOI: 10.21203/rs.3.rs-47873/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and validation of autophagy-related lncRNA prognostic signature for breast cancer

Abstract: Background: Long noncoding RNAs (lncRNAs) are emerging as crucial regulators to the development of breast cancer and are involved in controlling autophagy. LncRNAs are also widely known as valuable prognostic factors for breast cancer patients. It is critical to identify autophagy-related lncRNAs with prognostic value in breast cancer. Methods: A coexpression network of autophagy-related mRNAs-lncRNAs from The Cancer Genome Atlas (TCGA) was constructed. Univariate and multivariate Cox proportional hazards anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…Interestingly, Z68871.1 was highly expressed in the high-risk group of BC patients, whether in the risk model based on autophagy-related lncRNAs 24 or BCSCrelated lncRNAs. 25 These findings were consistent with our results in the forest plot that AC004585. and other 4 autophagy-related lncRNAs to build the prognostic risk model in BC and found that LINC01871 mainly enriched in low-risk group.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, Z68871.1 was highly expressed in the high-risk group of BC patients, whether in the risk model based on autophagy-related lncRNAs 24 or BCSCrelated lncRNAs. 25 These findings were consistent with our results in the forest plot that AC004585. and other 4 autophagy-related lncRNAs to build the prognostic risk model in BC and found that LINC01871 mainly enriched in low-risk group.…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, overexpression of oncogenic SEMA3B-AS1 is associated with poor survival outcomes in hepatocellular carcinoma and gastric cancer [31,32]. Furthermore, recent studies revealed that seven RBPrelated lncRNAs (LINC01871 [33], AC061992.1 [34], AL122010.1 [35], USP30-AS1 [36], Z68871.1 [33,35], AC245297.3 [35], and AP003119.3 [35]) included in the RBPLSig could be prognostic factors in some cancers. Nevertheless, the biological functions and the underlying molecular mechanisms of these lncRNAs in cancer have not yet been clarified.…”
Section: Discussionmentioning
confidence: 82%
“…22,23 Emerging studies have tried to establish novel and effective lncRNAs pattern risk models in malignancy, 24,25 as well as discover molecular character and potential therapy targets of breast cancer patients. 26,27 Until now, the patterns of necroptosis-related lncRNAs in BC and the potential capability of predicting the prognosis has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%